Analisis Persepsi Modal, Prosedur Pinjaman, Jaminan, dan Tingkat Margin Dalam Pengajuan Pembiayaan UMKM di Bank Syariah Indonesia KCP. Tanjungbalai - Khoirun Niswah; Tuti Anggraini (Jurnal Ilmiah Ekonomi Islam, 2023)
The purpose of this study is to determine whether there are differences in perceptions between customers who apply for financing at Bank Syariah Indonesia Kcp Tanjungbalai. The variables used in this study are: Age, Type of Business, Operating Income, and Education and are based on four aspects, namely Capital Aspects, Financing Procedure Aspects, Guarantee Aspects and Margin Level Aspects. This type of research uses a quantitative approach and uses the analysis of the Kruskall Wallis Test. The population in this study was all MSME actors who became customers at Bank Syariah Indonesia Kcp Tanjungbalai with a total sample taken of 30 people using Purposive Sampling. The results of this study show that there are differences in perceptions between customers in applying for MSME financing at BSI Kcp Tanjungbalai. Namely from the factor of the type of business, and the level of age. Meanwhile, the education factor and the business income factor showed different results where there was no difference in perception in applying for MSME financing at BSI Kcp Tanjungbalai.